KEWENANGAN NOTARIS DAN PPAT DALAM PROSES PEMBERIAN HAK GUNA BANGUNAN ATAS TANAH HAK MILIK - Dhenita Sari, I Gusti Agung; Wairocana, I Gusti Ngurah; Karma Resen, Made Gde Subha (Acta Comitas, 2018)
The existence of Article 15 of paragraph (2) letter f UUJNP regarding the authority of Notary to make deed related to land has led to various kinds of interpretation. The provisions Article of 15 paragraph (2) paragraph letter f  UUJNP authorize the Notary to make deeds relating to land but not explicitly regulate the limits of the authority of Notary to the authority of PPAT especially in the process of making the Deed related to the Granting Building Rights the Property. The obscurity of the norm in interpreting the meaning of the article also creates a conflict of authority in its implementation. Therefore, the problem of this research is related to the limitation of Notary Authority over PPAT Authority in the Process of Land Use Right Use Right under the applicable law and the meaning of the provisions of Article 15 of paragraph (2) letter f UUJNP stating the authority of Notary in making related deed with land.           This thesis research is a normative legal research w hich departed from the vague of norm. This thesis research used 3 type of approach. There are  statute approach, conseptual approach and analytical approach. The legal materil collection techniques used were the study of literature and card system. The analysis of the legal materials was conducted by using descriptive techniques and arguments associated with the theories and concepts of law which relevant to the issues. The research findings of the problem under study, namely, that is studied is the Limitation of Notary's authority over the authority of PPAT in the process of Granting Building Rights the Property  is Notary only authorized to extend the Deed of Introduction Agreement on the Granting Building Rights the Property. While the meaning of article 15 paragraph (2) letter f is a Notary authorized to make deed related to land. Notary authority in making land deed is during and as long as it is not a land deed which has been the authority of PPAT, in other words the Notary is not authorized to make deeds of transfer of land rights, transfer of ownership rights over the apartment, and the imposition of land rights.   Keywords: Notary Authority, Building Rights, Freehold Land